Ga-based van der Waals room temperature ferromagnetic crystal materials, their preparation and applications

Ga-based van der Waals room temperature ferromagnetic crystal materials, with optimized composition and synthesis, overcome the limitations of low Curie temperatures and magnetic properties in existing two-dimensional magnetic crystals, enabling the development of advanced quantum devices that can operate effectively at room temperature.

JP2025511696AActive Publication Date: 2025-04-16HUAZHONG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024559114
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-07-19
Filing Date
2022-12-03
Publication Date
2025-04-16
Estimated Expiration
2042-12-03

AI Technical Summary

Technical Problem

Current two-dimensional van der Waals magnetic crystals have low Curie temperatures, limiting their application to temperatures significantly below room temperature, and lack large saturation magnetic moments and perpendicular magnetic anisotropy.

Method used

The development of Ga-based van der Waals room temperature ferromagnetic crystal materials, specifically Fe3-aGa bTe2 and Fe5-cGeGa dTe2, with carefully controlled composition and synthesis methods to achieve high Curie temperatures, large saturation magnetic moments, and significant perpendicular magnetic anisotropy.

Benefits of technology

The resulting Ga-based van der Waals ferromagnetic crystals exhibit Curie temperatures ranging from 330 to 367K, saturation magnetic moments of 50 to 88.5 emu/g, and perpendicular magnetic anisotropy values up to 4.79×10^5 J/m^3, making them suitable for multifunctional two-dimensional quantum devices operating at room temperature.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511696000001_ABST
    Figure 2025511696000001_ABST
Patent Text Reader

Abstract

The present invention discloses Ga-based van der Waals room temperature ferromagnetic crystal material, its manufacture and application, which belongs to the technical field of nanoparticle magnetic material manufacture. 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d Te2 (c=-0.2~0.2, d=0.01~0.5). Fe 3-a Ga b The growth method of Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) is a self-supporting flux method in which excess Ga and Te are used as fluxes to grow the crystal. 5-c GeGa d The growth method of Te2 (c=-0.2~0.2, d=0.01~0.5) is a chemical vapor transport method using elemental iodine as a transport agent for growing the crystal. The Ga-based van der Waals room temperature ferromagnetic crystal Fe 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The composition of the Te2 (c=-0.2~0.2, d=0.01~0.5) material is uniform, has a van der Waals structure, and is easy to mechanically peel off. The Curie temperatures are 330~367K and 320~345K, respectively, and the saturation magnetic moments are 50~57.2emu / g and 80~88.5emu / g, respectively. Fe 3-a Ga b The perpendicular magnetic anisotropy of Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) single crystal is 3.25 × 10 5 ~4.79×10 5 J / m 3 It has also reached
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a technology for producing nanoparticle magnetic materials, and more particularly to Ga-based van der Waals room temperature ferromagnetic crystal materials, their production and applications. [Background technology]

[0002] Magnetism, which arises from the movement and spin rotation of charged elementary particles, has brought about a scientific revolution in key technologies such as data storage and biomedical imaging, and will continue to bring about new phenomena in the development of new materials and device miniaturization. Ferromagnetic materials can exhibit ferromagnetic ordered states in three-dimensional space, but the search for unique ferromagnetic materials in two-dimensional systems is difficult due to the theoretical limit of the Mermin-Wagner theorem. This theorem rigorously proves that long-range magnetic order is not possible in two-dimensional isotropic Heisenberg spin systems because thermodynamic fluctuations destroy all ordered states. Until recently, experimental research on two-dimensional ferromagnetic materials has made groundbreaking progress. In the last few years alone, CrI3, Cr2Ge2Te6, Fe n Ferromagnetic ordering phenomena have been observed using two-dimensional van der Waals crystals with van der Waals structures such as GeTe2 (n=3, 4, 5). This series of two-dimensional van der Waals ferromagnetic crystals and their heterostructures not only contain rich physical mechanisms and intriguing electronic properties, but also open up new research fields for various unusual quantum effects such as the quantum anomalous Hall effect and the quantum anomalous Hall effect, and are expected to provide a material foundation for realizing multifunctional quantum devices.

[0003] However, although the recently discovered two-dimensional van der Waals intrinsic magnetic crystals have promoted the development of intrinsic two-dimensional magnetism and various multifunctional spintronic devices, such as tunneling electron magnetic detection, spin quantum sensors, giant tunneling magnetoresistance, and spin electronics, these devices can still only work at temperatures well below room temperature, because the Curie temperatures of all of them are very low. Therefore, it remains a challenge to fabricate intrinsic two-dimensional van der Waals magnetic crystals with super-room-temperature Curie temperatures, large saturation magnetic moments, and large perpendicular magnetic anisotropy, and to realize operational two-dimensional quantum devices based on them. Summary of the Invention [Problem to be solved by the invention]

[0004] The object of the present invention is to provide a Ga-based van der Waals room temperature ferromagnetic crystal material and a manufacturing method thereof for solving the above-mentioned problems. 3-a Ga b Te2 (a=-0.3~0.1, b=0.8~1.2) and Fe 5-c GeGa d It is possible to produce high-quality Ga-based van der Waals room-temperature ferromagnetic crystals of Te2 (c=-0.2 to 0.2, d=0.01 to 0.5). 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The crystals of Te2 (c = -0.2 to 0.2, d = 0.01 to 0.5) all have a van der Waals structure, can be easily peeled off into a few layers (few layers), have Curie temperatures of 330 to 367 K and 320 to 345 K, respectively, which are higher than room temperature, and have saturation magnetic moments of 50 to 57.2 emu / g and 80 to 88.5 emu / g, respectively. 3-a Ga b The perpendicular magnetic anisotropy of Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) single crystal is 3.25 × 10 5 ~4.79×10 5 J / m 3Mechanical exfoliation can also be used to obtain two-dimensional Fe 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The thickness of the Te2 (c=-0.2 to 0.2, d=0.01 to 0.5) nanosheet is on the nanometer scale, and the lateral size is on the micrometer scale, so it is suitable for various current micro-nano processing technologies and can be used to fabricate various multifunctional two-dimensional quantum devices. Furthermore, the manufacturing method of the Ga-based van der Waals room temperature ferromagnetic crystal material of the present invention is simple, low cost, and has good process stability. The present invention is expected to contribute to the development and practical application of various multifunctional two-dimensional quantum devices based on Ga-based two-dimensional van der Waals room temperature ferromagnetic crystals.

[0005] In accordance with a first aspect of the present invention, there is provided a Ga-based van der Waals ferromagnetic crystal material, the ferromagnetic crystal material being Fe 3-a Ga b A ferromagnetic crystal material having a value of Te2, a=-0.3 to 0.1, and b=0.8 to 1.2, or the ferromagnetic crystal material is Fe 5-c GeGa d The ferromagnetic crystal material is Te2, c=-0.2 to 0.2, and d=0.01 to 0.5. 3-a Ga b Te2 ferromagnetic crystal Fe 3-a Ga b Te2 compounds and the Fe 5-c GeGa d Te2 ferromagnetic crystal Fe 5-c GeGa d All of the Te2 compounds contain an iron atom with a valence of zero, and the Fe 3-a Ga b Te2 ferromagnetic crystals and the Fe 5-c GeGa d The Curie temperatures of the Te ferromagnetic crystals are 330 to 367 K and 320 to 345 K, respectively. 3-a Ga b Te2 ferromagnetic crystals and the Fe 5-c GeGa dTe2 ferromagnetic crystals exhibit magnetism below their respective Curie temperatures. Preferably, the Fe 3-a Ga b Te2 ferromagnetic crystals and Fe 5-c GeGa d The saturation magnetic moments of Te2 ferromagnetic crystals are 50-57.2 emu / g and 80-88.5 emu / g, respectively. In another aspect of the present invention, there is provided a method for producing a ferromagnetic crystal, comprising the steps of: (1) uniformly and thoroughly mixing Fe powder, Ga blocks and Te powder, the sum of the amounts of substance of the Fe powder and the Ga blocks being equal to the amount of substance of the Te powder, and the amount of substance of the Fe powder being 40% to 60% of the sum of the amounts of substance of the Fe powder and the Ga blocks; evacuating a vessel containing the mixture obtained in the step (1); (2) heating the mixture to a heating temperature of 950 to 1050°C, cooling after heating, and cooling at a rate of 0.5 to 1.5°C / h during a crystal growth process; 3-a Ga b and step (3) of obtaining Te2 ferromagnetic crystals, in which a=-0.3 to 0.1 and b=0.8 to 1.2. Preferably, the heating time is 24 to 48 hours. Preferably, the temperature is decreased by first quenching to 880° C. at a rate of 70 to 170° C. / h, then slowly cooling to 780° C. at a rate of 0.5 to 1.5° C. / h, and then naturally cooling. In another aspect of the present invention, there is provided a method for producing a ferromagnetic crystal, comprising: step (1) of uniformly and thoroughly mixing Fe powder, Ge powder, Ga block, Te powder and I2 particles, a ratio of the amount of substance of the Fe powder, the sum of the amounts of substance of the Ge powder and the Ga block and the amount of substance of the Te powder is 4:1:2, and the amount of substance of the Ge powder is 40% to 60% of the sum of the amounts of substance of the Ge powder and the Ga block; evacuating a vessel containing the mixture obtained in step (1); step (2) of placing a portion of the vessel containing the mixture in a high-temperature raw material zone in a dual-temperature zone tubular furnace and placing a portion of the vessel not containing the mixture in a low-temperature crystallization zone in a dual-temperature zone tubular furnace, a temperature of the high-temperature raw material zone being 950 to 1050°C and a temperature of the low-temperature crystallization zone being 600 to 700°C, the I2 particles being used as a transport agent, and transporting the mixture to a low-temperature crystallization zone to react to produce Fe 5-c GeGa d and step (3) of obtaining Te2 magnetic crystals, in which c=-0.2 to 0.2 and d=0.01 to 0.5. Preferably, in step (3), the reaction time is 168 hours to 330 hours. Preferably, the mass of I2 particles relative to the volume of the container is 3 to 9 mg / cm 3 . In another aspect of the present invention, there is provided an application of the Ga-based van der Waals magnetic crystal material in a two-dimensional quantum device. Preferably, the two-dimensional quantum device is an anomalous Hall device or an electrically controlled magnetic device. Effect of the Invention

[0006] Compared with existing technologies, the technical solution of the present invention mainly has the following technical advantages:

[0007] (1) Fe grown by slow cooling to near the crystallization temperature using the self-flux method 3-a Ga bThe single crystals of the Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) block are highly pure and easy to peel off, allowing two-dimensional nanosheets with a few layers (few layers) to be obtained. Their size is suitable for micro- and nano-processing techniques such as photolithography, making them suitable for the fabrication of various multifunctional two-dimensional quantum devices.

[0008] (2) Using the chemical vapor transport method, Fe was grown in the low-temperature crystallization zone of a quartz ampoule at a constant temperature with iodine as the transport agent. 5-c GeGa d Te2 (c=-0.2~0.2, d=0.01~0.5) single crystals are highly pure and easy to peel off, allowing two-dimensional nanosheets with a few layers (few layers) to be obtained. Their size is suitable for micro- and nano-processing techniques such as photolithography, making them suitable for the fabrication of various multifunctional two-dimensional quantum devices.

[0009] (3) Iron 3-a Ga b In the case of Te2 (a=-0.3 to 0.1, b=0.8 to 1.2), since a sufficient excess of Ga and Te is required as a flux to dissolve Fe, which has a high melting point, the ratio of the raw material usage amounts described in the claims is adopted. Among them, Ga plays a more important role, so the relationship between the substance amounts of Fe and Ga in the raw materials is further defined. Fe 5-c GeGa d In the case of Te2 (c=-0.2 to 0.2, d=0.01 to 0.5), the efficiency with which the iodine element transports the four elements involved in the compound is different, so the ratio of the raw material usage amounts described in the claims is adopted. For example, Ga is more difficult to transport than Ge, so the compound Fe 5-c GeGa d Even if the amount of Ga in Te2 (c = -0.2 to 0.2, d = 0.01 to 0.5) is much less than that of Ge, it is necessary to add excess Ga to the raw material.

[0010] (4) Ga-based van der Waals room temperature ferromagnetic crystal Fe produced by the present invention 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-cGeGa d The Curie temperatures of single crystals of Te2 (c = -0.2 to 0.2, d = 0.01 to 0.5) are 330 to 367 K and 320 to 345 K, respectively. This ultra-room temperature ferromagnetism comes from the zero-valent iron atoms contained in both materials, Fe 3-a Ga b Te2 (a=-0.3~0.1, b=0.8~1.2) magnetic crystal Fe 3-a Ga b In the compound Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2), one iron atom is zero-valent, and the theoretical value of the Curie temperature of the zero-valent iron atom (i.e., elemental iron) reaches 1043 K. However, in the compound, Fe 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The difference in the crystal structure of Te2 (c = -0.2 to 0.2, d = 0.01 to 0.5) single crystals and elemental iron reduces the Curie temperature, but it is still above 300 K, higher than most known van der Waals magnetic crystals.

[0011] (5) The Ga-based van der Waals room temperature ferromagnetic crystals produced by the present invention all have a large saturation magnetic moment. 3-a Ga b The saturation magnetic moment of single crystal Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) is 50 to 57.2 emu / g, and Fe 5-c GeGa d The saturation magnetic moment of Te2 (c = -0.2 to 0.2, d = 0.01 to 0.5) single crystals is 80 to 88.5 emu / g, which is higher than most known two-dimensional van der Waals magnetic crystals.

[0012] (6) Ga-based van der Waals room temperature ferromagnetic crystal Fe produced by the present invention 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) has a large perpendicular magnetic anisotropy, which is 3.25 × 10 at 300 K. 5 ~4.79×10 5 J / m 3and higher than most widely used ferromagnetic thin film materials.

[0013] (7) Iron 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The two-dimensional nanosheets obtained by mechanically exfoliating single crystals of Te2 (c=-0.2~0.2, d=0.01~0.5) have a size on the micrometer scale and a thickness on the nanometer scale. These nanosheets are suitable for micro- and nano-fabrication processes such as material photolithography, and can be used to realize anomalous Hall elements and electrically controlled magnetic elements, and are expected to have a wide range of applications in the field of two-dimensional quantum devices. [Brief description of the drawings]

[0014] [Figure 1] 1 shows an X-ray diffraction pattern of a Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe3GaTe2 single crystal in embodiment 1. [Diagram 2] 13 is an X-ray diffraction pattern of a Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe5GeGa0.1Te2 single crystal in embodiment 4. [Diagram 3] FIG. 2 is an energy spectrum element distribution diagram of a Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe3GaTe2 nanosheet in embodiment 1. [Figure 4] FIG. 11 is an energy spectrum element distribution diagram of a Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe5GeGa0.1Te2 nanosheet in embodiment 4. [Diagram 5] 1 shows the spontaneous magnetization curve, out-of-plane magnetic field, and hysteresis curves at different temperatures of a Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe3GaTe2 single crystal in embodiment 1. [Figure 6] 13 shows the spontaneous magnetization curve, out-of-plane magnetic field, and hysteresis curve at different temperatures of the Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe5GeGa0.1Te2 single crystal in the fourth embodiment. [Figure 7]FIG. 2 is a diagram showing an anomalous Hall element of a Ga-based two-dimensional van der Waals room-temperature ferromagnetic crystal Fe3GaTe2 nanosheet in embodiment 1 and the ultra-room-temperature anomalous Hall effect. [Figure 8] FIG. 13 is a diagram showing an anomalous Hall element and ultra-room temperature anomalous Hall effect of a Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe5GeGa0.1Te2 nanosheet in embodiment 4. [Figure 9] FIG. 1 is a diagram showing a hysteresis loop at an in-plane magnetic field of 300 K for a Ga-based two-dimensional van der Waals room-temperature ferromagnetic crystal Fe3GaTe2 single crystal in the first embodiment. [Figure 10] FIG. 2 is an electrically controlled magnetization curve diagram of a Ga-based two-dimensional van der Waals room-temperature ferromagnetic crystal Fe3GaTe2 single crystal in embodiment 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to describe the present invention and are not intended to limit the present invention. In addition, the technical features according to various embodiments of the present invention described below can be combined with each other as long as they are not mutually inconsistent.

[0016] The present invention provides a Ga-based van der Waals room temperature ferromagnetic crystal material and a method for producing the same, and the method for producing the material is as follows.

[0017] Fe 3-a Ga b About Te2 (a=-0.3~0.1, b=0.8~1.2) 1) Step 1: Fe powder (purity 99.99%), Ga block (purity 99.999%), and Te powder (purity 99.999%) in a specific molar ratio are placed in the bottom of a quartz ampoule. The specific molar ratio means that the sum of the amounts of substance of the Fe powder and the Ga block is equal to the amount of substance of the Te powder, and in this embodiment, the amount of substance of the Fe powder accounts for 40% to 60% of the sum of the amounts of substance of the Fe powder and the Ga block.

[0018] 2) Step 2: Vacuum and seal the ampoule.

[0019] 3) Step 3: The ampoule is placed in a muffle furnace, the temperature is raised to 950-1050°C within 1-5 hours, the temperature is maintained for 1-2 days, then it is rapidly cooled to 880°C, and slowly cooled to 780°C at a rate of 0.5-1.5°C / h. After that, the program (execution step) ends, and the ampoule is naturally cooled to room temperature in the muffle furnace.

[0020] Fe 5-c GeGa d About Te2 (c=-0.2~0.2, d=0.01~0.5) 1) Step 1: A specific molar ratio of Fe powder (purity 99.99%), Ge powder (purity 99.999%), Ga block (purity 99.999%), Te powder (purity 99.999%), and a specific mass of I2 particles (purity 99.99%) are placed in the bottom of a quartz ampoule. The specific molar ratio means that the ratio of the amount of substance of the Fe powder, the sum of the amounts of substance of the Ge powder and the Ga block, and the amount of substance of the Te powder is 4:1:2, and in this embodiment, the amount of substance of the Ge powder accounts for 40% to 60% of the sum of the amounts of substance of the Ge powder and the Ga block.

[0021] 2) Step 2: Vacuum and seal the ampoule. 3) Step 3: Place the ampoule in a dual temperature zone tubular furnace (a tubular furnace with two heating zones). The raw material end is the high temperature raw material zone (high temperature zone), and the other end is the low temperature crystallization zone (low temperature zone). Within 1 to 5 hours, the high temperature zone and the low temperature zone are heated to 950 to 1050°C and 600 to 700°C, respectively, and then cooled naturally to room temperature after keeping the temperature for 1 to 2 weeks.

[0022] In one embodiment, the Ga block has a size of 1 to 10 mm and a volume of 0.1 to 0.5 cm. 3 The diameter of the I2 particles is in the range of 1 to 3 mm, and the mass of the I2 particles relative to the volume of the container is in the range of 3 to 9 mg / cm. 3 The size of the Fe, Ge, and Te powders is 100 to 300 mesh.

[0023] In one embodiment, the process of evacuating and sealing the quartz tube (vacuum sealing process) is as follows: evacuate the quartz tube to 1 Pa or less using a mechanical pump, flush with argon gas with a purity of 99.999% three times to remove oxygen from the quartz tube, and finally seal the glass tube with an oxyhydrogen flame.

[0024] In some embodiments, Fe 3-a Ga b The diameter of the quartz ampoule for growing Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) is 2 cm and the length is 10 cm. 5-c GeGa d The tube diameter of the quartz ampoule for growing Te2 (c = -0.2 to 0.2, d = 0.01 to 0.5) is 2 to 5 cm and the length is 40 cm.

[0025] In one embodiment, the Fe 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The sizes of the crystal materials of Te2 (c = -0.2 ~ 0.2, d = 0.01 ~ 0.5) are 2 ~ 3 × 1 ~ 2 × 0.1 ~ 0.5 mm and 6 × 4 × 0.1 ~ 0.5 mm, respectively.

[0026] The Ga-based van der Waals room temperature ferromagnetic crystal material and the Fe 3-a Ga b Te2 (a = -0.3 to 0.1, b = 0.8 to 1.2) and Fe 5-c GeGa d The ferrocrystalline materials of Te2 (c=-0.2~0.2, d=0.01~0.5) are all high-quality room-temperature ferromagnetic compounds with van der Waals structure, which can be easily mechanically peeled off into two-dimensional nanocrystals with silvery white color, flat surface and relatively thin thickness. Therefore, the present invention can be used to fabricate multifunctional two-dimensional quantum devices, and the materials are all single crystals.

[0027] The Ga-based van der Waals room-temperature ferromagnetic crystal material and the manufacturing method of the present invention will be described in detail below with reference to the specific embodiments and drawings. EMBODIMENT 1 1) High purity Fe powder, Ga block, and Te powder are weighed out in a molar ratio of 1:1:2, placed at the bottom of a quartz ampoule, and then evacuated and sealed.

[0028] 2) The sealed ampoule is placed in a muffle furnace. It is heated to 1000°C over an hour, kept at that temperature for a day, rapidly cooled to 880°C at a rate of 100°C / h, and then slowly cooled to 780°C at a rate of 1°C / h. The process is then terminated, and the ampoule is naturally cooled to room temperature in the furnace to obtain a single crystal of Fe3GaTe2. EMBODIMENT 2 1) High purity Fe powder, Ga block, and Te powder are weighed out in a molar ratio of 0.8:1.2:2, placed at the bottom of a quartz ampoule, and then evacuated and sealed.

[0029] 2) The sealed ampoule is placed in a muffle furnace. It is heated to 1000°C over 1 hour, kept at that temperature for 1 day, rapidly cooled to 880°C at a rate of 100°C / h, and slowly cooled to 780°C at a rate of 1°C / h. The process is then terminated, the ampoule is naturally cooled to room temperature in the furnace, and the Fe 2.9 Ga 1.2Obtain a single crystal of Te2. EMBODIMENT 3 1) High purity Fe powder, Ga block, and Te powder are weighed out in a molar ratio of 1.2:0.8:2, placed at the bottom of a quartz ampoule, and then evacuated and sealed.

[0030] 2) The sealed ampoule is placed in a muffle furnace. It is heated to 1000°C over 1 hour, kept at that temperature for 1 day, rapidly cooled to 880°C at a rate of 100°C / h, and slowly cooled to 780°C at a rate of 1°C / h. The process is then terminated, the ampoule is naturally cooled to room temperature in the furnace, and the Fe 3.3 Ga 0.8 Obtain a single crystal of Te2. EMBODIMENT 4 1) High-purity Fe powder, Ge powder, Ga block, Te powder and 0.3 g I2 particles are weighed out in a molar ratio of 8:1:1:4, placed at the bottom of a quartz ampoule, and then vacuum sealed.

[0031] 2) The sealed ampoule is placed in a dual temperature zone tubular furnace, with the raw material end being the high temperature raw material zone (high temperature zone) and the other end being the low temperature crystallization zone (low temperature zone). Within an hour, the high temperature zone and the low temperature zone are heated to 1000°C and 650°C, respectively, and kept at these temperatures for two weeks. After that, the zone is naturally cooled to room temperature, and the Fe5GeGa 0.1 Obtain a single crystal of Te2. EMBODIMENT 5 1) High-purity Fe powder, Ge powder, Ga block, Te powder and 0.3 g I2 particles are weighed out in a molar ratio of 8:1.2:0.8:4, placed at the bottom of a quartz ampoule, and then vacuum sealed.

[0032] 2) The sealed ampoule is placed in a dual temperature zone tubular furnace, with the raw material end being the high temperature raw material zone (high temperature zone) and the other end being the low temperature crystallization zone (low temperature zone). Within an hour, the high temperature zone and the low temperature zone are heated to 1000°C and 650°C, respectively, and kept at these temperatures for two weeks. After that, the zone is naturally cooled to room temperature, and the Fe2O3 is crystallized in the crystallization zone. 5.2 GeGa 0.01 Obtain a single crystal of Te2. EMBODIMENT 6 1) High-purity Fe powder, Ge powder, Ga block, Te powder and 0.3 g I2 particles are weighed out in a molar ratio of 8:0.8:1.2:4, placed at the bottom of a quartz ampoule, and then vacuum sealed.

[0033] 2) The sealed ampoule is placed in a dual temperature zone tubular furnace, with the raw material end being the high temperature raw material zone (high temperature zone) and the other end being the low temperature crystallization zone (low temperature zone). Within an hour, the high temperature zone and the low temperature zone are heated to 1000°C and 650°C, respectively, and kept at these temperatures for two weeks. After that, the zone is naturally cooled to room temperature, and the Fe2O3 is crystallized in the crystallization zone. 4.8 GeGa 0.5 Obtain a single crystal of Te2.

[0034] Figure 1 shows the X-ray diffraction pattern of Fe3GaTe2 single crystal. Compared with the theoretical X-ray diffraction pattern, the evenly spaced diffraction peaks in the X-ray diffraction pattern of Fe3GaTe2 single crystal correspond to the (001) crystal plane, and no impurity peaks are observed. This indicates that the synthesized Fe3GaTe2 single crystal has high crystal quality and strict growth orientation. Figure 2 shows the Fe5GeGa 0.1 The X-ray diffraction pattern of Te2 single crystal. Compared with the theoretical X-ray diffraction pattern, Fe5GeGa 0.1 The evenly spaced diffraction peaks in the X-ray diffraction pattern of Te2 single crystal correspond to the (001) crystal plane, and no impurity peaks are observed. This is because the Fe5GeGa 0.1 The results show that the Te2 single crystal has high crystal quality and strict growth orientation. Figure 3 shows the energy spectrum element distribution map of the Fe3GaTe2 nanosheet. The energy spectrum analysis shows that the three elements Fe, Ga, and Te are uniformly distributed in the Fe3GaTe2. Figure 4 shows the Fe5GeGa 0.1 The energy spectrum element distribution map of Te2 nanosheet. The energy spectrum analysis shows that the four elements Fe, Ge, Ga, and Te are Fe5GeGa 0.1Figure 5 shows the spontaneous magnetization curves, out-of-plane magnetic fields, and hysteresis curves at different temperatures of the Fe3GaTe2 single crystal, which indicate that the Fe3GaTe2 single crystal has inherent ultra-room-temperature ferromagnetism and a large saturation magnetic moment. 0.1 Spontaneous magnetization curves, out-of-plane magnetic field, and hysteresis curves at different temperatures for Te2 single crystals, and Fe5GeGa 0.1 The results show that the single crystal of Fe3GaTe2 has the inherent room-temperature ferromagnetism and large saturation magnetic moment. Figure 7 shows the anomalous Hall element and room-temperature anomalous Hall effect of the Fe3GaTe2 nanosheet, demonstrating the easy peeling property, inherent room-temperature ferromagnetism, and potential application in two-dimensional quantum devices of the single crystal of Fe3GaTe2. Figure 8 shows the Fe5GeGa 0.1 The anomalous Hall effect of Te2 nanosheets and the room temperature anomalous Hall effect of Fe5GeGa 0.1 The figures show the easy peeling characteristics of the Te2 single crystal, its inherent ultra-room temperature ferromagnetism, and the applicability to two-dimensional quantum devices. Figure 9 shows the in-plane magnetic field and hysteresis curves at 300 K of the Ga-based two-dimensional van der Waals room temperature ferromagnetic crystal Fe3GaTe2 single crystal in embodiment 1. This figure shows that the perpendicular magnetic anisotropy of Fe3GaTe2 at 300 K is 4.79 × 10 5 J / m 3 It can be calculated that the magnetization curve of the Ga-based two-dimensional van der Waals room-temperature ferromagnetic crystal Fe3GaTe2 single crystal in the first embodiment is electrically controlled. This shows that the current flowing through the device has a large tuning effect on the Hall resistance of the sample, indicating the possibility of application in the field of two-dimensional quantum devices.

[0035] Those skilled in the art can understand that the above description is only a preferred embodiment of the present invention, and does not limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A Ga-based van der Waals magnetic crystal material, the magnetic crystal material being Fe 3-a G b Te 2 , a=-0.3 to 0.1, b=0.8 to 1.2, or the magnetic crystal material is Fe 5-c GeGa d Te 2 , c=-0.2 to 0.2, d=0.01 to 0.5; The Fe 3-a G b Te 2 Magnetic crystal Fe 3-a G b Te 2 Compound and the Fe 5-c GeGa d Te 2 Magnetic crystal Fe 5-c GeGa d Te 2 All of the compounds contain an iron atom with a valence of zero, The Fe 3-a G b Te 2 Magnetic crystals and the Fe 5-c GeGa d Te 2 The Curie temperatures of the magnetic crystals are 330 to 367 K and 320 to 345 K, respectively. 3-a G b Te 2 Magnetic crystals and the Fe 5-c GeGa d Te 2 The magnetic crystals are Ga-based van der Waals magnetic crystal materials, which are characterized in that they exhibit magnetism at or below their respective Curie temperatures.

2. The Fe 3-a G b Te 2 Magnetic crystals and Fe 5-c GeGa d Te 2 2. The Ga-based van der Waals magnetic crystal material according to claim 1, wherein the saturation magnetic moment of the magnetic crystal is 50 to 57.2 emu / g and 80 to 88.5 emu / g, respectively.

3. A method for producing magnetic crystals, comprising the steps of: Step (1): thoroughly mixing Fe powder, Ga block, and Te powder, wherein the sum of the amounts of substance of the Fe powder and the Ga block is equal to the amount of substance of the Te powder, and the amount of substance of the Fe powder is 40% to 60% of the sum of the amounts of substance of the Fe powder and the Ga block; Step (2) of subjecting a vessel containing the mixture obtained in step (1) to a vacuum; The mixture is heated to a heating temperature of 950 to 1050° C., and cooled after heating. During the crystal growth process, the temperature is lowered at a rate of 0.5 to 1.5° C. / h. 3-a G b Te 2 A method for producing magnetic crystals, comprising: a step (3) of obtaining magnetic crystals, in which a=-0.3 to 0.1, and b=0.8 to 1.

2.

4. 4. The method for producing magnetic crystals according to claim 3, wherein the heating time is 24 to 48 hours.

5. The method for producing magnetic crystals according to claim 3, characterized in that the temperature is first rapidly cooled to 880°C at a rate of 70 to 170°C / h, then slowly cooled to 780°C at a rate of 0.5 to 1.5°C / h, and then naturally cooled.

6. A method for producing magnetic crystals, comprising the steps of: Fe powder, Ge powder, Ga block, Te powder and I 2 Step (1), in which the particles are thoroughly mixed, and the ratio of the amount of substance of the Fe powder, the sum of the amount of substance of the Ge powder and the Ga block, and the amount of substance of the Te powder is 4:1:2, and the amount of substance of the Ge powder is 40% to 60% of the sum of the amount of substance of the Ge powder and the Ga block; Step (2) of subjecting a vessel containing the mixture obtained in step (1) to a vacuum; The portion of the vessel containing the mixture is placed in a hot feed zone in a dual temperature zone tubular furnace, and the portion of the vessel not containing the mixture is placed in a cold crystallization zone in a dual temperature zone tubular furnace, the hot feed zone having a temperature of 950-1050° C. and the cold crystallization zone having a temperature of 600-700° C., 2 The particles are used as a transport agent to transport the mixture to a low temperature crystallization zone and react to form Fe 5-c GeGa d Te 2 A method for producing magnetic crystals, comprising: a step (3) of obtaining magnetic crystals, in which c=-0.2 to 0.2 and d=0.01 to 0.

5.

7. 7. The method for producing magnetic crystals according to claim 6, wherein in step (3), the reaction time is 168 hours to 330 hours.

8. I vs. container volume 2 The mass of the particles is 3 to 9 mg / cm 3 7. The method for producing a magnetic crystal according to claim 6 .

9. 3. Application of the Ga-based van der Waals magnetic crystal material according to claim 1 or 2 in a two-dimensional quantum device.

10. 10. The application of claim 9, wherein the two-dimensional quantum device is an anomalous Hall device or an electrically controlled magnetic device.